Friction between Archwire of Different Sizes, Cross Section, Alloy and Brackets Ligated with Different Brands of Low Friction Elastic Ligatures- An Invitro Study - Bhushan Patil (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Friction in orthodontic treatment does exist and is thought to reduce the efficiency of orthodontic appliances during sliding mechanics. During sliding mechanics, a friction force is produced at the bracket archwire-ligature unit which tends to counteract the applied force and in turn resists the desired movement. Aim: The aim of this invitro study was to determine the friction between archwire of different sizes, cross section, alloy and brackets ligated with different brands of low friction elastic ligatures. Materials and Methods: An 0.022-in slot, 10 stainless steel brackets and various orthodontic archwires which were ligated with low-friction ligatures and subjected to evaluate frictional resistance i.e. static friction and dynamic friction. The archwires of 0.014” and 0.016” nickel titanium (NiTi), 0.016 × 0.022” stainless steel (SS), 0.017 × 0.025” NiTi, 0.017 × 0.025” SS, 0.017 × 0.025” titanium molybdenum alloy (TMA), 0.019 × 0.025” SS were used. Each bracket/archwire combination was evaluated 10 times at room temperature of 27 ± 2ºC. The study groups included Group I of conventional round shape module with reduced friction coating i.e. super slick and synergy and Group II contained figure of “8” shape module i.e. Octavia ties and Slide ligature. Result: The mean static friction force and dynamic friction force for all 7 types of wires was lower in Group II (C, D) combined compared to Group I (A, B) and the difference was statistically very highly significant (p<0.001). Conclusion: Super slick and synergy can be used in the initial and final phase of treatment when full engagement of archwire in the bracket slot is necessary for proper tip and torque expression. Slide and Octavia ties modules can be used in the premolar brackets during en mass retraction when using friction mechanics.